Pathogenesis of Isolated Newcastle Disease Virus Genotype VII .1.1 in Turkey Poults in Egypt - M. E. Hegazy, Ahmed; Abd El-Fattah Bedair, Amr; M. N. Tolba, Hala (Journal of Advanced Veterinary Research, 2022)
Recurrent infection with Newcastle disease virus in flocks that have received vaccinations and high economic losses in Egypt in the last few years urged us to study the diversity and genetic changes in isolated NDV from chickens and its pathogenesis in other species such as turkey poults. Fifteen positive NDVs were isolated from chicken flocks suffering from a respiratory infection. Sequencing of three isolates out from the 15 NDV positive isolates (20%) revealed that NDV was genotype VII.1.1. When compared to other previously isolated worldwide and Egyptian strains, the three isolates’ amino acid sequences show (99.1-99.8 %) identity with genotype VII.1.1.Thirty four weeks old Black Burzi turkey poults, separated into two groups: control (n=15) and infected (n=15), were used to study the pathogenesis of the isolated NDV genotype VII.1.1. Each afflicted bird was given an inoculation with 0.1 mL of 106EID50 of NDV genotype VII.1.1( ND /chicken /Egypt /Dakahlia /31 /2020) at 4 weeks of age via an ocular route. Proventriculus, conjunctiva, lung, spleen, trachea, and caecal tonsil samples were collected from both groups at (6, 12, 24, 48 hours, and 5 days after infection) and tested for the presence of NDV using Quantitative Reverse transcription-polymerase Chain Reaction (QRT-PCR). The virus was found in the challenged birds’ spleen as soon as 12 hours after infection, followed by the lungs and trachea. After 2 and 5 days after NDV infection, histologically significant lesions were found, particularly in lymphoid organs. It is concluded that the presence of NDV in Egyptian flocks of chickens could induce major disease in commercial turkeys, necessitating the development of novel vaccinations based on the circulating NDV genotype VII.1.1 in Egypt to protect domestic poultry from recurrent infection.